(untitled) (Bangladesh Journal of Medicine, 2022)
Background: The aim and objective of this study was to compare the effectiveness between mannitol and sodium phosphate as a colonoscopic bowel cleansing agent conducted in the department of Gastroenterology of Sir Salimullah Medical College Mitford Hospital. Methods: In this cross-sectional study, a total number of 108 cases were randomly selected, who underwent colonoscopy from November 2019 to June 2020 in the department of Gastroenterology of Sir Salimullah Medical College and Mitford Hospital. The patients were divided into two groups based on received bowel preparations agent, either mannitol (Group MN) or sodium phosphate (group NaP). Results: Out of 108 patients 57 received mannitol and 51 received sodium phosphate. Thirty-two males and twenty-two females received mannitol, while 28 males and 23 females received sodium phosphate. Excellent bowel preparation was observed in 32(55%) cases of MN group and 26(45%) cases of group NaP. No statistically significant difference between two groups by Chi-square (X2) test (p=0.793). Conclusion: This cross-sectional, randomized study did not show any significant statistical difference between the two agents regarding effectiveness of bowel preparation. So, both mannitol and sodium phosphate are almost equally effective in achieving excellent or good quality of bowel preparation. Bangladesh J Medicine 2022; 33: 263-268